The Effect Of Auditor Experience And Professional Skepticism On Fraud Detection With Workload As A Moderating Variable - Nicholla Anggelita Adinda Elta; Margareta Yosefa Meilani (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to determine the effect of auditor experience and professional skepticism on fraud detection with workload as a moderating variable. Design/methodology/approach – This research uses quantitative research. This research was conducted using a questionnaire distributed to project admins, staff and PIC projects at PT. Deksha Orla Tranggana, namely 39 questionnaires distributed via social media in the form of whatsapp. Each questionnaire distributed has 35 questions to be answered by respondents. From the distribution of questionnaires carried out, 30 respondents were obtained. To get the results of this study, this researcher used PLS SEM Version 3.0 Findings – The results of this study indicate that the auditor experience variable has a positive and insignificant effect on fraud detection, professional skepticism has a positive and significant effect on fraud detection, workload does not strengthen the effect of auditor experience on fraud detection, and workload strengthens the effect of professional skepticism on fraud detection. Research limitations/implications – This research focuses on fraud detection, which is to see how the right way to deal with fraud when you already have work experience and relate it to the workload given but must maintain a skeptical attitude towards an examination.